Optimal Utility Pricing when Consumers Form Habits : The Case of Piped Water in Vietnam - Do, Quy-Toan (World Bank, Washington, DC, 2020)
As utility services expand throughout the developing world, providers must grapple with how to set prices to recover average costs. Data from a multi-year randomized pricing experiment among nearly 1500 recently-connected piped water customers in Vietnam reveal month-to-month demand persistence. Based on structural demand estimation, the authors document how endogenous preferences, if unaccounted for, can lead to low take-up and thereby threaten the financial viability of the new water utility. They also show that such demand persistence, while distinct from credit constraints, calls for pricing schemes that similarly defer payment, effectively allowing future consumers to subsidize their present selves.